Improving Ray Tracing Anti-aliasing Performance through Image Gradient Analysis - Teixeira, João Marcelo X. N.; Albuquerque, Eduardo S.; Santos, Artur L. dos; Teichrieb, Veronica; Kelner, Judith (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2010)
Ray tracing is the primary technique used for imaging based on the simulation of physical phenomena. The core problem is in the need of high computing power. Since the 1960s, research has been conducted to improve the efficiency of algorithms and the development of parallel systems has promoted their implementation. Migration to many-core architectures and in particular the development of GPUs make realtime applications possible. This work aims at improving the performance of ray tracing with support for anti-aliasing using image processing techniques implemented in GPU. The results show considerable gains with the use of the proposed approach.